PENGARUH PENANAMAN MODAL ASING TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Fajar Bimantoro; Mona Adriana S (Media Ekonomi, 2016)
The present study aimed to analyze the relationship between the level of foreign direct investment to Indonesia's economic growth in the period 1991-2014.Fokus of the present study was to analyze the short-term relationship between foreign direct investment and economic growth Indonesia. In addition, along with the financial crisis 2008 global bit much negative of Indonesia affected by the global economic slowdown due to the crisis. This prompted the present study was to also perform forecasting of the impact of global financial crisis on foreign direct investment and relation to economic growth. To answer these questions, this research chose VAR Vector Auto Regression or as a method to answer the research questions. Gross Domestic Product (GDP), Consumer Price Index, BI rate, and the Exchange Rate, the variables used in this research. The estimation results of the VAR indicate that direct investment from abroad did not have an impact on economic growth in the long term but has a strong bond in the short term against the growth of economics. This indicates that foreign investment into Indonesia increasingly quality in promoting economic growth. In addition, the results of forecasting using impulse response function indicates there will be the tendency of a decrease in the level of foreign direct investment and economic growth in Indonesia.